2019
DOI: 10.17576/pengurusan-2019-57-13
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ Remuneration, Firm Performance and Political Connection: Evidence from State-Owned Enterprise (SOE) in Malaysia

Abstract: The objective of this paper is to examine the relationship between directors' remuneration and firm performance among state-owned enterprise (SOE) in Malaysia. In addition, we examine whether board size and government's role moderate the relationship between directors' remuneration and firm performance in SOE. Using panel data regression model on 118 firm-year observations of state-owned enterprise in Malaysia from 2011 to 2013, this study finds there is positive relationship between directors' remuneration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…In 2018, no publication was found on firm performance. In 2019, one publication on firm performance was found, i.e., in the study by Marzuki and Shukri (2019) investigating Malaysia's state-owned enterprises (SOEs). They revealed that firm performance is closely related to directors' remuneration, indicating that incentives for directors work well in monitoring activities.…”
Section: Trend Topicsmentioning
confidence: 99%
“…In 2018, no publication was found on firm performance. In 2019, one publication on firm performance was found, i.e., in the study by Marzuki and Shukri (2019) investigating Malaysia's state-owned enterprises (SOEs). They revealed that firm performance is closely related to directors' remuneration, indicating that incentives for directors work well in monitoring activities.…”
Section: Trend Topicsmentioning
confidence: 99%